Interpretation of prescription from the perspective of elderly patients functional and low schools (Research, Society and Development, 2021)
The theme of our paper circumscribes discussions around the elderly patient, and we focus on the prescription genre, which is generated in different layers of the health areas. The study aimed to: Identify, through bibliographic review, how the prescription is being understood by the functional illiterate elderly patient or with low education. An integrative review was carried out, and the inclusion criteria for the selection of studies were selected only original articles in full text, within the six-year time frame and in Brazilian Portuguese, with abstracts indexed in the selected databases and the time frame six years (2015 to 2020). As one of the main results, we have that patients who attend health units more often and have a bond with the professional, present a better response to treatment, making the proposal to create the professional bond proposed by the Family Health Strategy (FHS) and Primary Health Care (PHC).